2014
DOI: 10.4236/ajps.2014.521346
|View full text |Cite
|
Sign up to set email alerts
|

Production and Quality of Menthol Mint Essential Oil and Antifungal and Antigerminative Activity

Abstract: Agricultural products certified as organic and free of pesticides cannot use synthetic chemicals in the production process. In this context, the search for new natural products appears as an alternative to the use of conventional pesticides, aiming to combat agricultural diseases. Menthol is a natural product obtained from plants that has importance in different branches of industry, mainly due to the feeling of freshness it provides in contact with skin and mucous. Menthol (70%-90%) is the main compound of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
3
8
0
1
Order By: Relevance
“…Components with high percentage were: α-Phellandrene (3.22%), Dl-Limonene (1.48%), linalool (2.22%), Linalool (2.22%), cis-Piperitone oxide (3.63%), Menthone (29.42%), neo-Menthol (4.75%), Eucalyptol (6.95%), Isomenthone (10.85%), Menthol (21.35%), and Thymol (1.64%) and some other components with small amount were also identified. Our results agree with that of Souza et al [7] they showed the presence of menthol (67.27%) and menthone (13.34%) in highest amount in young leaves of M. arvensis. In another study, researcher showed the presence of 25 different components in the essential oil of M. arvensis in which the higher concentration was observed of menthol and menthone [7].…”
Section: Chemical Composition Of Essential Oilsupporting
confidence: 93%
See 3 more Smart Citations
“…Components with high percentage were: α-Phellandrene (3.22%), Dl-Limonene (1.48%), linalool (2.22%), Linalool (2.22%), cis-Piperitone oxide (3.63%), Menthone (29.42%), neo-Menthol (4.75%), Eucalyptol (6.95%), Isomenthone (10.85%), Menthol (21.35%), and Thymol (1.64%) and some other components with small amount were also identified. Our results agree with that of Souza et al [7] they showed the presence of menthol (67.27%) and menthone (13.34%) in highest amount in young leaves of M. arvensis. In another study, researcher showed the presence of 25 different components in the essential oil of M. arvensis in which the higher concentration was observed of menthol and menthone [7].…”
Section: Chemical Composition Of Essential Oilsupporting
confidence: 93%
“…Our results agree with that of Souza et al [7] they showed the presence of menthol (67.27%) and menthone (13.34%) in highest amount in young leaves of M. arvensis. In another study, researcher showed the presence of 25 different components in the essential oil of M. arvensis in which the higher concentration was observed of menthol and menthone [7]. Some researcher showed that the percentage of chemical component in essential oil can vary in different cultivar of mint and at different growing stage [16].…”
Section: Chemical Composition Of Essential Oilsupporting
confidence: 93%
See 2 more Smart Citations
“…Biological activity in regarding to essential oil from those species against fungi, bacteria and insects were reported, as wel. 22,[39][40][41][42][43]…”
Section: Introductionmentioning
confidence: 99%